"Do female anime fans exist?" The impact of women-exclusionary discourses on rec.arts.anime. Issue 4 (12th December 2022) - Petit, Aurélie
Abstract: This paper examines women-exclusionary discourses on the popular anime Usenet newsgroup, rec.arts.anime. By going back to pre-2000 online anime histories, this paper proposes to understand how women-exclusionary discursive practices on rec.arts.anime have contributed to shaping contemporary toxic technocultures' discursive identities, as it is admitted that forum 4chan originated from online anime fandom. By using a data set of 252 messages related to gender issues posted from 1992 to 1996, I identify 7 discursive practices that I am theorizing here under the name of negative networking: 1. Blaming female anime fans for their lack of visibility; 2. Doubting the authentic interest of women in anime; 3. Mystifying the female anime fan; 4. Harassing female anime fans; 5. Criticizing the association of feminism with anime, both as interpretive practices and as scholarship; 6. Belittling female anime fans' concerns; and 7. Denying or ignoring the challenges faced by female anime fans. I argue that the impact of these discourses must be understood as determinant in the establishment of the online anime hegemonic fan identity and its prediscourses, especially as they relate to the long-lasting marginalization of women and gender diverse anime fans.